Long-Term Results of a Phase 2 Study of Definitive Chemoradiation Therapy Using S-1 for Esophageal Squamous Cell Carcinoma Patients Who Were Elderly or With Serious Comorbidities - Chen, Yun; Zhu, Zhengfei; Zhao, Weixin; Liu, Qi; Zhang, Junhua; Deng, Jiaying; Ai, Dashan; Lu, Saiquan; Jiang, Liuqing; Tseng, Ihsuan; Jia, Huixun; Zhao, Kuaile (Frontiers in Oncology, 2022)
BACKGROUND: The optimal evidence-based management for the subsets of locally advanced esophageal squamous cell carcinoma (ESCC) patients who rejected or were intolerant to intravenous chemotherapy due to old age or serious comorbidities is currently lacking. This study aimed to assess the safety and local control rate (LCR) of S-1 (tegafur-gimeracil-oteracil potassium) combined with radiotherapy in these subsets of ESCC patients. METHODS: Locally advanced ESCC patients who rejected or were intolerant to intravenous chemotherapy due to aged > 75 years or serious comorbidities were enrolled in a prospective, single-arm, phase 2 trial. The patients were treated with definitive concurrent chemoradiotherapy with S-1, which was administered orally twice daily for 28 days. The radiotherapy dose was 61.2 Gy delivered in 34 fractions. The primary end-point was the 3-year LCR. This trial was registered with ClinicalTrials.gov, number NCT01831531. RESULTS: One hundred five ESCC patients were recruited between March 2013 and October 2015. At the median follow-up of 73.1 months (IQR 65.5-81.4 months), 3-year LCR was 61.1%, and 1, 3, and 5-year overall survival was 77.9%, 42.3%, and 24.8% respectively. For safety analysis, ≥ grade 3 acute adverse events included thrombocytopenia (6.7%), leukopenia (2.9%), anemia (1.0%), anorexia (1.0%), fatigue (10.5%), hiccup (1.0%), pneumonitis (4.8%), and esophagitis (3.8%). Two patients (1.9%) died of late esophageal hemorrhage, and one patient (1.0%) died of late radiation-induced pneumonitis. CONCLUSION: S-1 is a promising regimen in concurrent chemoradiotherapy with low toxicity and a favorable LCR in ESCC patients who rejected or were intolerant to intravenous chemotherapy due to old age or serious comorbidities.